UHF/VHF INTERNET TV BROADCASTING SYSTEM - Attiqa, R.; Hanif, A.; Akram, A. (The Nucleus, 2013)
The internet has a great impact on information broadcasting. It provides greater storage capacity and fulfills the requirement of mobility that satisfy human desires. With this broadband service, Internet users can watch video contents all over the world. Conventional Televisions are not capable of receiving digital video streams like the streams from the internet. In our research work, we have developed a system such that TV can be made capable of receiving digital streams after converting it in analog format. This converted analog video is transmitted using high power TV transmitter.